How to make frozen yogurt : 56 delicious flavors you can make at home / Nicole Weston - Weston, Nicole
Most recipes produce a hard frozen yogurt that's not much fun to eat, but with Weston's unique technique-- using a simple meringue and your ice cream maker-- the result is creamy, smooth, and delicious. Weston then offers recipes for irresistible flavors, including festive flavors for the holidays, including candy cane, spiced pumpkin, cranberry, eggnog, and gingerbread.